2014
DOI: 10.1371/journal.pone.0114465
|View full text |Cite
|
Sign up to set email alerts
|

Light-Limited Growth Rate Modulates Nitrate Inhibition of Dinitrogen Fixation in the Marine Unicellular Cyanobacterium Crocosphaera watsonii

Abstract: Biological N2 fixation is the dominant supply of new nitrogen (N) to the oceans, but is often inhibited in the presence of fixed N sources such as nitrate (NO3 −). Anthropogenic fixed N inputs to the ocean are increasing, but their effect on marine N2 fixation is uncertain. Thus, global estimates of new oceanic N depend on a fundamental understanding of factors that modulate N source preferences by N2-fixing cyanobacteria. We examined the unicellular diazotroph Crocosphaera watsonii (strain WH0003) to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Additional data are derived from separate measurement of size and growth: these are shown as light lines centred at the mean and arms covering range. These are for the pico-prokaryotes (green) Prochlorococcus and Synechococcus (Morel et al, 1993;Johnson et al, 2006;Christaki et al, 1999;Moore et al, 1998;Agawin and Agustí, 1997) and the diazotrophs (light blue) Crocosphaera and Trichodesmium (Garcia and Hutchins, 2014;Webb et al, 2009;Wilson et al, 2017;Bergman et al, 2013;Boatman et al, 2017;Breitbarth et al, 2008;Hutchins et al, 2007;Kranz et al, 2010;Shi et al, 2012). of group-specific accessory pigments) and scattering of light. The absorption spectra are flatter with larger sizes following Finkel and Irwin (2000) to account for self-shading, and scattering spectra are also influenced by size following Stramski et al (2001) (see Text S1.3, Fig.…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data are derived from separate measurement of size and growth: these are shown as light lines centred at the mean and arms covering range. These are for the pico-prokaryotes (green) Prochlorococcus and Synechococcus (Morel et al, 1993;Johnson et al, 2006;Christaki et al, 1999;Moore et al, 1998;Agawin and Agustí, 1997) and the diazotrophs (light blue) Crocosphaera and Trichodesmium (Garcia and Hutchins, 2014;Webb et al, 2009;Wilson et al, 2017;Bergman et al, 2013;Boatman et al, 2017;Breitbarth et al, 2008;Hutchins et al, 2007;Kranz et al, 2010;Shi et al, 2012). of group-specific accessory pigments) and scattering of light. The absorption spectra are flatter with larger sizes following Finkel and Irwin (2000) to account for self-shading, and scattering spectra are also influenced by size following Stramski et al (2001) (see Text S1.3, Fig.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The simulation uses Monod kinetics, and C : N : P : Fe stoichiometry is constant over time (though it differs between phytoplankton groups). Chl a for each phytoplankton type varies in time and space depending on light, nutrient and temperature conditions following Geider et al (1998). Following empirical evidence, mixotrophic dinoflagellates are assumed to have lower maximum photosynthetic growth rates than other phytoplankton of the same size (Tang, 1995;Fig.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Additional data are derived from separate measurement of size and growth: These are shown as light lines centered at the mean and arms covering range. These are for the pico-prokaryotes (green) Prochlorococcus and Synecochoccus (Morel et al, 1993, Johnson et al 2006, Christaki et al 1999, Moore et al 1998, Agawin and Agustí 1997 and the diazotrophs (light blue) Crocosphera and Trichodesmium (Garcia and Hutchins, 2014;Webb et al, 2009;Wilson et al, 2017;Bergman et al, 2013;Boatman et al 2017;Beithbarth et al, 2008;Hutchins et al 2007;Kranz et al, 2010;Shi et al, 2012). Figure 11: Sensitivity simulations, model annual mean richness for trait dimensions.…”
Section: Author Contributionmentioning
confidence: 99%
“…The negative correlation with ammonia may be an indication of the type of N 2 ‐fixation inhibition by ammonia that was observed in Crocosphaera culture experiments (Dekaezemacker and Bonnet, ; Garcia and Hutchins, ). Those studies found that the effect of N 2 ‐fixation inhibition was stronger under low light growth conditions (Garcia and Hutchins, ) and also stronger in large cell strains compared with small cell strains (Dekaezemacker and Bonnet, ). Given those results, it is notable that there was a dominance of large cells in deeper water where ammonia concentrations are higher and light levels are lower.…”
Section: Discussionmentioning
confidence: 85%